Deutsche Literatur im polnischen Literaturunterricht - Orłowski, Hubert (Studia Germanica Posnaniensia, 2018)
Although the presence of German language literature in handbooks and readers used in teaching literature in high schools and technical schools has undergone the evolution within the last fifty years, it has not changed so much as not being able to determine several relevant characteristics of its presence. (The above mentioned applies also to the reading list.) There are three features which seem to be especially distinctive for establishing the place of German language literature in teaching: 1. the German literature emerges everywhere where it is an argument for the existence of the world literature (Goethe, Schiller); 2. writers whose works influenced the Polish literature, and who made friends with Polish writers are eagerly referred to during the lectures on history of literature; 3. Those writers whose works preserve the essential cultural and philosophical issues (Kafka, Thomas Mann, Brecht), occupy a prominent place in a projected picture of the world Jilerature. The polilical, social and ideological changes taking place in Poland nowadays, have also flourished with rather essential changes in the programme of teaching literature. However, it has not been so essential as to make noticeable changes in the adopting of German literature.